SP0082 Glycosylation of Anti-Nuclear Autoantibodies Determines Their Inflammatory Potential. (9th June 2015) - Herrmann, M.
Abstract : The Fc portion of IgG harbours a single glycosylation site. Glycan sialylation is critical for structure and for certain effector functions of IgG. Anti-histone-IgG of patients with systemic lupus erythemathosus is reportedly responsible for the recruitment of polymorphonuclear cells (PMN) to the clearance of apoptotic cells. Autoantibodies decorating Secondary NEcrotic Cells (SNEC) induce pro-inflammatory responses after activation of blood-borne phagocytes. Analyzing the sialylation status of affinity purified anti-histone-IgG in patients with SLE we demonstrated anti-histone-IgG preferentially contained in the desialylated fraction. In functional ex vivo phagocytosis studies, desialylated anti-SNEC-IgG preferentially directed SNEC into PMN but did not change their cytokine secretion profiles. In contrast, sialylated IgG reduced the phagocytosis by monocytes of SNEC. Moreover, the sialylated anti-SNEC-IgG was not simply anti-inflammatory but switched the cytokine secretion profiles from IL6/IL8 to TNFα/IL1β. Here we described how different sialylation statuses of IgG autoantibodies contribute to the complex inflammatory network that regulates chronic inflammation. Disclosure of Interest: None declared